2016
DOI: 10.5487/tr.2016.32.3.177
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Cancer Metabolism - Revisiting the Warburg Effects

Abstract: After more than half of century since the Warburg effect was described, this atypical metabolism has been standing true for almost every type of cancer, exhibiting higher glycolysis and lactate metabolism and defective mitochondrial ATP production. This phenomenon had attracted many scientists to the problem of elucidating the mechanism of, and reason for, this effect. Several models based on oncogenic studies have been proposed, such as the accumulation of mitochondrial gene mutations, the switch from oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 170 publications
0
85
0
4
Order By: Relevance
“…In addition to surviving the hypoxic environment within a tumor, cancer cells predominantly use glycolysis both in aerobic and hypoxic environments (Vander Heiden et al, 2009, Tran et al, 2016). Altered isoforms and abnormal expression of glycolytic enzymes have been proposed as ways to achieve higher rates of glycolysis observed in cancer cells (Atsumi et al, 2002; Bustamante et al, 1981; Cairns et al, 2011; Christofk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to surviving the hypoxic environment within a tumor, cancer cells predominantly use glycolysis both in aerobic and hypoxic environments (Vander Heiden et al, 2009, Tran et al, 2016). Altered isoforms and abnormal expression of glycolytic enzymes have been proposed as ways to achieve higher rates of glycolysis observed in cancer cells (Atsumi et al, 2002; Bustamante et al, 1981; Cairns et al, 2011; Christofk et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Targeting the metabolic differences between cancer and normal cells holds promise as a novel anti-cancer strategy [77]. Cancer cells usually use high level of ATP for their enhanced glycolytic metabolism (Warburg effect, [78]). Distinct UNBS1450mediated in vitro growth inhibitory effects between normal and cancer cells seemed to be correlated with a lower ATP level in cancer than in normal cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…As the study found out the protein rather form complex with the anti-apoptotic Bcl-2 protein myeloid cell leukemia-1 (Mcl-1) and stimulates improved glucose metabolism and enhances metabolism via the PPP, favoring synthesis ribose sugar and NADPH. Furthermore, subsequent studies showed that over expression of NOXA in tumor cells, and over activity of CDK5 to promote tumor growth and survival, specifically in thyroid and neuroendocrine tumors [46,47].…”
Section: Bcl-2 Proteinsmentioning
confidence: 99%
“…In addition to activation of oncogenes and loss of tumor suppressor pathways, mutations in key metabolic enzymes as well as preferential expression of specific isoforms of metabolic enzymes can provide cancer cells a mechanism to select for metabolic alterations during tumorigenesis [3,8,48].…”
Section: Metabolic Enzymesmentioning
confidence: 99%